The effect of feeding rate on the growth performance of green sturgeon (Acipenser medirostris) fry. (16th October 2014) - Zheng, K.K.; Deng, D.F.; De Riu, N.; Moniello, G.; Hung, S.S.O.
Abstract Four one‐week growth trials were conducted on green sturgeon fry to determine the effect of feeding rate on their growth performance at 18 °C when they were fed a salmonid soft moist feeds containing 445–457 g kg−1 of crude protein and 201–207 g kg−1 of lipid. The fry used in Trials I‐IV were 5–8 weeks after their initiation of exogenous feeding. Their average initial body weights were 1.63 ± 0.01, 2.63 ± 0.03, 5.08 ± 0.08 and 7.49 ± 0.05 g, respectively. Six feeding rates used were as follows: 2.5–15.0% body weight per day (% BW day−1) with a 2.5% increment in Trial I; 1.25–7.50% BW day−1 with a 1.25% increment in Trial II; and 2.0–7.0% BW day−1 with a 1.0% increment in Trials III and IV. Four replicates with 50 fry per tank in Trials I‐III and 30 fry per tank in Trial IV were assigned randomly to each feeding rates. The final body weight, specific growth rate, feed efficiency, protein retention, and whole‐body moisture, lipid, and energy contents were significantly (P < 0.05) affected by the feeding rates. The optimum feeding rates determined by the broken‐line model were 7.1, 5.7 and 5.3% BW day−1 for Trials I, II and IV, when the fry were 5, 6 and 8 weeks after their initiation of exogenous feeding, respectively.